Increased Nitric Oxide and Attenuated Diastolic Blood Pressure Variability in African Americans with Mildly Impaired Renal Function - Keith M. Diaz; Deborah L. Feairheller; Kathleen M. Sturgeon; Praveen Veerabhadrappa; Sheara T. Williamson; Deborah L. Crabbe; Michael D. Brown (International Journal of Hypertension)
We investigated the relationship between renal function, blood pressure variability (BPV), and nitric oxide (NO) in a group of African Americans with normal or mildly impaired renal function. 24-hour ambulatory blood pressure monitoring was performed, NO measured, and glomerular filtration rate (GFR) calculated in 38 African Americans. Participants were categorized as having normal (GFR > 90 mL/min per 1.73 m2) or mildly impaired (GFR 60–89 mL/min per 1.73 m2) renal function. Diastolic BPV was significantly lower in the mildly impaired renal function group. Regression analyses revealed a significant positive association between GFR and diastolic BPV for the entire study group. Plasma NO levels were significantly higher in the mildly impaired renal function group and negatively correlated with diastolic BPV. In conclusion, diastolic BPV was reduced in African Americans with mildly impaired renal function, which may be the result of increased NO production. These results conflict with previous findings in diseased and nonblack populations and could provide rationale for studying BPV early in the disease state when BP-buffering mechanisms are still preserved.